Subclasses of Analytic Functions Defined by Generalized Hypergeometric Functions. (31st January 2016) - Alkahtani, Badr S.; Mustafa, Saima; Bulboacă, Teodor
Abstract : We introduce a new subclass of analytic functions in the unit disk U, defined by using the generalized hypergeometric functions, which extends some previous well-known classes defined by different authors. Inclusion results, radius problems, and some connections with the Bernardi-Libera-Livingston integral operator are discussed.